Measurement and modeling of diameter distributions of particulate matter in terrestrial solutions. Issue 7 (11th April 2013) - Levia, Delphis F.; Michalzik, Beate; Bischoff, Sebastian; Näthe, Kerstin; Legates, David R.; Gruselle, Marie‐Cecile; Richter, Susanne
Abstract : [1] Particulate matter (PM) plays an important role in biogeosciences, affecting biosphere‐atmosphere interactions and ecosystem health. This is the first known study to quantify and model PM diameter distributions of bulk precipitation, throughfall, stemflow, and organic layer (Oa) solution. Solutions were collected from a European beech ( Fagus sylvatica L.) forest during leafed and leafless periods. Following scanning electron microscopy and image analysis, PM distributions were quantified and then modeled with the Box‐Cox transformation. Based on an analysis of 43, 278 individual particulates, median PM diameter of all solutions was around 3.0 µm. All PM diameter frequency distributions were skewed significantly to the right. Optimal power transformations of PM diameter distributions were between −1.00 and −1.56. The utility of this model reconstruction would be that large samples having a similar probability density function can be developed for similar forests. Further work on the shape and chemical composition of particulates is warranted. Key Points: Particulate matter distributions significantly skewed to the right Median particulate diameter is near 3.0 microns with large difference in maxima Our model reconstructions can be readily used by others